2022
DOI: 10.1002/aenm.202201631
|View full text |Cite
|
Sign up to set email alerts
|

Engineering an Insoluble Cathode Electrolyte Interphase Enabling High Performance NCM811//Graphite Pouch Cell at 60 °C

Abstract: the fact that "the higher unsaturation, the larger merits". These unique properties contribute to the improved electrochemical performance of commercial NCM811/graphite pouch cells up to around 300 cycles with more than 85% capacity retention at 60 °C, along with the LCO cells reaching ≈90% capacity retention over 350 cycles. We hope these findings can provide guidelines for designing functional electrolyte additives for better aggressive battery chemistries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 81 publications
0
58
0
Order By: Relevance
“…8C). 141 The results demonstrated that bonds with higher degrees of unsaturation and highly reactive sites exhibited more polymerization through three-dimensional topological routes to form an insoluble CEI on the cathode, which contributed to the inhibition of parasitic reactions and TM crosstalk.…”
Section: Suppressing the Mobility Of Crosstalk Speciesmentioning
confidence: 94%
See 1 more Smart Citation
“…8C). 141 The results demonstrated that bonds with higher degrees of unsaturation and highly reactive sites exhibited more polymerization through three-dimensional topological routes to form an insoluble CEI on the cathode, which contributed to the inhibition of parasitic reactions and TM crosstalk.…”
Section: Suppressing the Mobility Of Crosstalk Speciesmentioning
confidence: 94%
“…37,72 In situ infrared and Raman spectroscopy techniques offer unique advantages in the identification of organic and inorganic components in the SEI, CEI, and electrolyte. 141,158 In view of the complexities of battery structure and components, a multiscale theoretical model based on molecular dynamics simulations, multiphysics field simulations, and machine learning techniques will be helpful for better probing crosstalk mechanisms. [159][160][161] In addition, the flexible use of reference electrodes (three-electrode or fourelectrode cells) will provide much convenience when studying the effects of crosstalk on battery behaviors.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Obviously, the cell with ATMS exhibited a resistance lower than that of the counterpart without additive, confirming that the Li + deposition is facilitated by the ATMS-derived SEI film. Conclusively, the preferential oxidation/reduction of ATMS will affect the reactions of the carbonates due to the unsaturated carbon–carbon double bond (CC), and then the properties of the resulting CEI/SEI film are tuned. , …”
Section: Resultsmentioning
confidence: 99%
“…Conclusively, the preferential oxidation/ reduction of ATMS will affect the reactions of the carbonates due to the unsaturated carbon−carbon double bond (C�C), and then the properties of the resulting CEI/SEI film are tuned. 40,41…”
Section: Oxidation/reduction Behaviors Of Atmsmentioning
confidence: 99%
“…While for the battery working at a high temperature (>40 °C), the battery utilizes the stability of the LiDFP-derived SEI/CEI which is rich in inorganics, more robust, and thus can effectively suppress electron tunneling and TM dissolution [16] of the TM-based cathodes. [23,37] In addition to regulating SEI/CEI film compositions, Klein et al proposed a TM scavenging mechanism to illustrate why LiDFP significantly improved the battery performance. [9,31,39] PO 3 F 2− , the byproduct of LiDFP, would combine with TM ions in the electrolyte and precipitate, which prevented TM ions from diffusing to the SEI on the anode.…”
Section: Introductionmentioning
confidence: 99%